Impact of endometriosis on oocyte morphology in IVF-ICSI: retrospective study of a cohort of more than 6000 mature oocytes - Camille Robin; Audrey Uk; Christine Decanter; Hélène Behal; Pierre Collinet; Chrystèle Rubod; Anne-Laure Barbotin; Geoffroy Robin (BMC, 2021)
Abstract Background Infertility associated with endometriosis can be explained by several non-exclusive mechanisms. The oocyte plays a crucial role in determining embryonic competence and this is particularly relevant for in vitro fertilization (IVF) outcomes. According to some authors, the morphology of oocytes could also be a non-invasive marker of oocyte quality. The aim of this study was to evaluate the relationship between endometriosis and oocyte morphology after controlled ovarian stimulation for intracytoplasmic sperm injection (ICSI) on a large oocyte cohort. Methods Single-center comparative retrospective study in the academic In Vitro Fertilization (IVF) unit of the Lille University Hospital. A total of 596 women treated for IVF-ICSI with ejaculated spermatozoa for sperm alterations were included. They were classified as endometriosis (n = 175) or control groups (n = 401). The morphological evaluation of 2,016 mature oocytes from 348 cycles of patients with endometriosis was compared with that of 4,073 mature oocytes from 576 control cycles. The main outcome measures were Average Oocyte Quality Index (AOQI) and metaphase II oocyte morphological scoring system (MOMS). Comparison of groups was carried out by a mixed linear model and by a generalized estimation equation model with a "patient" random effect to consider that a patient might have several attempts. Results No difference in AOQI and MOMS scores was found between endometriosis and control women (adjusted p = 0.084 and 0.053, respectively). In case of endometriosis, there were significantly fewer metaphase II oocytes retrieved, embryos obtained, grade 1 embryos and number of cumulative clinical pregnancies compared to controls. In the endometriosis group, endometriosis surgery was associated with a reduced number of mature oocytes retrieved, and the presence of endometrioma(s) was associated with some abnormal oocyte shapes. Nevertheless, no difference concerning the AOQI and MOMS scores was found in these subgroups. Conclusion Endometriosis does not have a negative impact on oocytes' morphology in IVF-ICSI. Trial registration On December 16, 2019, the Institutional Review Board of the Lille University Hospital gave unrestricted approval for the anonymous use of all patients' clinical, hormonal and ultrasound records (reference DEC20150715-0002).